2018
DOI: 10.3233/mnm-180227
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract attenuates non alcoholic fatty liver disease by decreasing hyperlipidemia and enhancing Superoxide dismutase activity in cholesterol-fed rats

Abstract: BACKGROUND/AIM: Health benefits of green tea for a wide variety of ailments, including the cancer, heart disease, and liver disease, were reported. It is believed to have beneficial effects in the prevention and treatment of many diseases, one of which is non-alcoholic fatty liver disease (NAFLD). This study inspects the protective effect of green tea against atherosclerosis and NAFLD in comparative approach between curative and preventive models. MATERIALS AND METHODS: Twenty four of Wistar rats were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The aqueous extract of green tea alleviated NAFLD in C57BL/6 mice by modulating the expression of miR-34a and miR-194, resulting in increasing the expression of SIRT1, PPAR- α , and insulin-induced gene 2 (Insig2), as well as decreasing the expression of apolipoprotein a5, 3-hydroxy-3-methyl glutaryl coenzyme A synthase (HMG-CoA synthase), and HMG-CoA reductase [ 110 ]. Also, the consumption of the green tea extract alleviated hyperlipidemia and enhanced the activity of superoxide dismutase (SOD) in Wistar rats [ 113 ]. Moreover, oral gavage of green tea polyphenols could inhibit the hepatic lipogenesis in Zucker rats by upregulating the AMPK signaling pathway, with reducing the levels of insulin, glucose, ALT, AST, TNF- α , and interleukin-6 (IL-6) [ 114 ].…”
Section: Mechanisms Of Plant-based Foods and Their Bioactive Compomentioning
confidence: 99%
See 1 more Smart Citation
“…The aqueous extract of green tea alleviated NAFLD in C57BL/6 mice by modulating the expression of miR-34a and miR-194, resulting in increasing the expression of SIRT1, PPAR- α , and insulin-induced gene 2 (Insig2), as well as decreasing the expression of apolipoprotein a5, 3-hydroxy-3-methyl glutaryl coenzyme A synthase (HMG-CoA synthase), and HMG-CoA reductase [ 110 ]. Also, the consumption of the green tea extract alleviated hyperlipidemia and enhanced the activity of superoxide dismutase (SOD) in Wistar rats [ 113 ]. Moreover, oral gavage of green tea polyphenols could inhibit the hepatic lipogenesis in Zucker rats by upregulating the AMPK signaling pathway, with reducing the levels of insulin, glucose, ALT, AST, TNF- α , and interleukin-6 (IL-6) [ 114 ].…”
Section: Mechanisms Of Plant-based Foods and Their Bioactive Compomentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity dismutase (SOD) in Wistar rats [113]. Moreover, oral gavage of green tea polyphenols could inhibit the hepatic lipogenesis in Zucker rats by upregulating the AMPK signaling pathway, with reducing the levels of insulin, glucose, ALT, AST, TNF-α, and interleukin-6 (IL-6) [114].…”
mentioning
confidence: 99%
“…Total titratable acidity (TTA) was determined according to Wibowo et al (2015). Total sugar contents expressed as (mg/l) were determined according to Labdi et al (2018), calibration curve made of different solutions of glucose in water varying from 100 mg/L to 1,000 ml/l was used for the measure the results were extrapolated according the equation ( y = 0.0005 * x −0.0016, R 2 = .996).…”
Section: Methodsmentioning
confidence: 99%
“…28 Several other studies were by Suzuki et al reported methylated catechins direct the strong lipid-lowering activity in mice; Labdi et al confirmed the protective role of green tea intake in against atherosclerosis on hypercholesterol-fed rat; Ahmad et al reported the drinks supplemented with catechins and EGCG are effective against obesity, hypercholesterolemia and hyperglycemia in rats. 29,30,31…”
Section: In Vivo Studymentioning
confidence: 99%